Cyberbullying Experiences and Their Impact on Vocational Students’ Academic Achievement - Surya Jatmika; Khoirun Nafi'ah (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study investigates cyberbullying experiences among students in the Accounting program at SMK Negeri 3 Sukoharjo and their implications for psychological well-being and academic achievement. Responding to rising social media risks among adolescents, the research employs a qualitative case study design. Data were collected through semi-structured interviews, classroom observations, and documentation with victims of cyberbullying, guidance and counseling teachers, homeroom teachers, and the vice principal for student affairs. Data were analyzed using thematic analysis involving systematic coding, theme development, and interpretation, supported by source triangulation and member checking to enhance credibility. Findings indicate that cyberbullying—manifested as ridicule, negative comments, and unauthorized sharing of personal content—produces anxiety, diminished self-confidence, and social withdrawal. Consequently, affected students exhibit reduced concentration, lower classroom participation, and declining grades in several subjects. The study highlights the critical role of schools in mitigating cyberbullying by strengthening digital literacy, expanding counseling services, and establishing secure, sustainable reporting mechanisms. Recommendations emphasize integrated prevention strategies that involve teachers, parents, and school administrators to protect student welfare and support academic resilience.